A SPECIAL TRAINING COURSE «SECONDARY SCHOOL PRINCIPAL’S PROFESSIONAL TOLERANCE FORMATION DURING POSTGRADUATE TEACHER TRAINING» - Bryukhovetska, Oleksandra (PSYCHOLOGICAL JOURNAL, 2016)
The article substantiates the importance of formation of secondary school principal’s professional tolerance in the system of postgraduate education (refresher training). The author presents a special secondary school principal’s professional tolerance development training course and describes its components. The special course has two modules: a thematic discussion to form the trainee’s professional tolerance development readiness and a training course. The special course is meant for secondary school principal’s full time and distant refresher training in the system of postgraduate teacher education. The core of the special course includes the author’s developments (the results of her theoretical and empirical research and teaching-coaching). The innovative training forms and methods which included group discussions, business games, analysis of administrative situations, projects, round tables, experience sharing, trainings, etc., allowed avoiding a number of negative aspects of traditional education and making the training work comfortable, subject-subject, and interactive. The trainees develop skills and habits of analyzing their own management activities, finding ways out of difficult situations, solving complex management tasks, as well as become adaptive to rapidly changing conditions of reality and stress resistant. The secondary school principal’s professional tolerance formation course has been proved to be effective in institutions of postgraduate teacher education (refresher training). The special secondary school principal’s professional tolerance development training developed by the author has been proved effective in secondary school principal’s tolerance formation and provided a shift from the education for knowledge to the education for development, thus developing trainee’s tolerant interaction skills and readiness to be tolerant in professional activities.